IDENTIFIKASI POTENSI DAN PROGRAM PENGEMBANGAN PRODUK EKOWISATA DI DESA TIHINGAN, KECAMATAN BANJARANGKAN, KABUPATEN KLUNGKUNG - SUARKA, FANNY MAHARANI (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2011)
This research aims are to identify tourism potency in Tihingan village, and also to formulate the development strategy and programs of ecotourism development in Tihingan village. The principal approaches taken: were field observation, interview, and literature study. Method of data analyze used in this study are: Qualitative description mhetod and SWOT analysis The Research indicates that Tihingan object has natural beauty, in the form of rice field area, condition of rural environment; and social culture potency, such as: crafting of game/an, fossil in the is form of old prapen, inscription, monument, and traditional art of local community. Based of the result of SWOT analysis yield alternative strategy to develop Tihingan village as a ecotourism object; develop of facilities and basic facilities activity of tourism; promotion to hotel/travel agent; security alert strategy; and also to built the institutional management of the tourism object and increasing the quality of human resources. Development strategy of tourism object represents priority strategy that result program tourism object development by creating immeasurable attraction of tourism, maintaining the current condition of environment. The long-term success of tourism development depends upon sustaining a high quality resource base, both nature and culture. Levying of good tourism facilities and basic facilities, both are managed by local community and made in small capacities, which later can give contribution to local community. Promotions on Tihingan villages require to be improved, and in order to manage Tihingan villages as a ecotourism object should be established special institution.
Keywords: ecotourism, development, tourism based community